2017
DOI: 10.5152/iao.2016.2640
|View full text |Cite
|
Sign up to set email alerts
|

Association of Benign Paroxysmal Positional Vertigo with Osteoporosis and Vitamin D Deficiency: A Case Controlled Study

Abstract: OBJECTIVE:Benign paroxysmal positional vertigo (BPPV) is a common type of vertigo caused by the peripheral vestibular system. The majority of cases are accepted as idiopathic. Calcium metabolism also plays a primary role in the synthesis/absorption of otoconia made of calcium carbonate and thus might be an etiological factor in the onset of BPPV. In this study, we aimed to investigate the role of osteoporosis and vitamin D in the etiology of BPPV by comparing BPPV patients with hospital-based controls. MATERIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 27 publications
3
38
2
4
Order By: Relevance
“…Calcium is the main component of otoconia crystals and Vitamin D is required for its regulation (20). A series of clinical observational studies showed that vitamin D levels were decreased in BPPV (13,21,22). Compared with the non-cold season, there is less sunlight time and a lower ultraviolet index, leading to decreased vitamin D levels in the cold season.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is the main component of otoconia crystals and Vitamin D is required for its regulation (20). A series of clinical observational studies showed that vitamin D levels were decreased in BPPV (13,21,22). Compared with the non-cold season, there is less sunlight time and a lower ultraviolet index, leading to decreased vitamin D levels in the cold season.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Karataş et al (9) indicated that prevalence of osteoporosis and vitamin D deficiency is reasonably high in the general population, and the coexistence of BPPV with osteoporosis and vitamin D deficiency is coincidental. In a similar vein, Kahraman et al (10) indicated that vitamin D deficiency and decreased ionized Ca level may be a risk for BPPV, not only in patients with osteoporosis but also in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common type of vertigo caused by the peripheral vestibular system. It has been reported to affect women 2 times more often than men, and it is predominantly observed in postmenopausal women [1]. There is limited knowledge related to specific factors causing BPPV.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain predisposing factors include old age, whiplash injuries, and viral etiology. Recently, a familial tendency has also been identified as a predisposing factor for BPPV [1]. This Over the last 2 decades, several studies have been performed on the possible role of altered calcium metabolism in the pathogenesis of BPPV.…”
Section: Introductionmentioning
confidence: 99%